Anxiety and depression in the primary health care clinics and the use of complementary and alternative medicine - Taha, A.B.; Lee, PY; Lin, K; Syed Hassan, Al-Mashoor; Siti Raudzah, Ghazali (researchgate, 2005)
Objective: To determine the prevalence of depression and anxiety disorder in the primary care clinics in Kuching city and to examine the usage of complementary and alternative medicine (CAM) among the primary care patients who have psychiatric problems. Design: A cross-sectional survey design was used. Materials and Methods: This is a cross-sectional study of patients attending the primary care clinics. They were given core screening questionnaire, general questions on socio-demographic and questions pertaining to the usage of CAM. Patients who were positively screened for psychiatric problems will be interviewed by one of the researchers using the confirmatory questions. Results: The prevalence of all psychiatric problems in the primary care clinics was 16.6%. The commonest problem was depression at 6.7% prevalence rate followed by anxiety at 5.6%. 46.4% of the patients with psychiatric problems used CAM compared to only 20.8% of those without psychiatric problems. Significantly more patients with psychiatric problems consulted the Chinese temple medium or taking herbal medicine prescription.